An Examination of Accounting Student Background and Cognitive Ability: - Sargent, Matthew J; Winton, Bradley G (STIE Malangkucecwara, 2025)
The modern workplace demands ever-greater levels of cognitive ability. Corporations need newly hired graduates to enter the workplace with a certain level of critical thinking and reflective judgment skills. Unfortunately, accounting students appear to be falling behind in developing these cognitive skills. This research elaborates on the reflective judgment theory to investigate the backgrounds and cognitive levels of accounting students. The argument is made that certain background factors provide a significant differentiator among students’ reflective judgment and that students are below the necessary level of cognitive ability based on existing standards. Data from a study of accounting students in a United States-based university, tested with one-way Anova and dependent t-tests, support the role certain background factors play in student reflective judgment. The results also support the assertions that the cognitive abilities of graduating students do not meet the levels required by today’s corporations. These results suggest that accounting schools and accounting educators should employ more effective critical thinking curricula and assignments. This research adds to reflective judgment theory through a better understanding of student cognitive ability that can be translated into application in the classroom. Additionally, this research expands the use of open-ended structures in assessing cognitive abilities.